Is There A Significant Clinical Difference Between 2015 and 2019 AGS Beers Criteria in Terms of Inappropriate Drug Use: A Cross-Sectional Study - Şuayip Enes ARSLAN; Basri Furkan Dağcıoğlu (Ankara Medical Journal, 2020)
INTRODUCTION: It is aimed to determine the use of multiple drugs in patients aged 65 and over who are registered in the Home Health Unit, to determine whether the drugs are suitable according to the 2015 and 2019 AGS Beers Criteria, and to investigate whether there is a clinically significant difference between the two versions. METHODS: In our retrospective descriptive study, 659 patient files were scanned. The drug usage data of 493 patients, whose data were eligible, were analyzed according to the 2015 and 2019 AGS Beers criteria. RESULTS: The study included 493 patients, 354 (71.81%) of whom were female. The median number of diagnosed diseases was 6 (min: 1, max: 10), and the most common diseases were hypertension, generalized anxiety disorder, and diabetes mellitus. At least one drug used by 490 patients and the median number of drugs was 7 (min: 0, max: 16). Polypharmacy was detected in 306 (62.45%) patients and excessive polypharmacy in 91 (18.57%) patients. Potential Inappropriate Medication (PIM) status was determined in 211 patients according to 2015 and 2019 Beers criteria. PIM status was determined in 358 active substances according to the 2015 Beers Criteria and 383 active substances according to the 2019 Beers Criteria. The frequency of PIM was higher in patients with polypharmacy compared to both versions. DISCUSSION AND CONCLUSION: PIM status was observed to be significantly higher in patients with polypharmacy. When the PIM detection status of the 2015 and 2019 AGS Beers criteria was compared, inappropriateness was found in more active ingredients in the 2019 version.